2020
DOI: 10.1108/jrim-01-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent consumer factors, consequential branding outcomes and measures of online consumer engagement: current research and future directions

Abstract: Purpose The purpose of this study is to summarize the findings of consumer factor research and to suggest future lines of inquiry connected to branding outcomes. Consumers are comfortable with social media and accept firms occupying the same digital space. However, some consumers more readily engage with firms online than others. Consumer factor antecedents are numerous and yet not fully explored. Online consumer engagement has also been defined and measured in various ways. The resultant outcomes related to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 171 publications
(262 reference statements)
2
108
1
10
Order By: Relevance
“…Habibi, Laroche, and Richard (2016) found that while supporting the brand community with strategies such as content or incentives is necessary, the role and strength of brand community leaders, like market mavens, is more important for building a brand community. Market mavens have a strong online interaction propensity (Vander Shee, Peltier, & Dahl, 2020) which can lead to higher brand engagement (Dessart, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Habibi, Laroche, and Richard (2016) found that while supporting the brand community with strategies such as content or incentives is necessary, the role and strength of brand community leaders, like market mavens, is more important for building a brand community. Market mavens have a strong online interaction propensity (Vander Shee, Peltier, & Dahl, 2020) which can lead to higher brand engagement (Dessart, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Consumer engagement is a crucial factor in evaluating brands' advertising success on social media platforms (Peltier et al, 2020;Van Doorn et al, 2010). It has been variously defined over the years as a multi-dimensional concept involving cognitive, emotional, and behavioral aspects (Brodie et al, 2013;Gluck, 2013).…”
Section: Consumers' Behavioral Engagement On Social Mediamentioning
confidence: 99%
“…There is slight doubt that social media have gained growing acceptance among consumers that brands occupy these media as digital platforms (e.g. Qin, 2020;Vander Schee, et al, 2020). Online brand communities, as a social media type, strengthen consumer-brand bonds and improve the brand performance (Liao, and Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%